Pengaruh Penambahan Cacahan Limbah Plastik HDPE (High Density Polyethylene) Sebagai Bahan Tambah Campuran Laston AC-WC (Asphalt Concrete-Wearing Course) Terhadap Karakteristik Marshall - Ndun, Kezia Dwi Putri Natalia; Koreh, Andreas Welem; Lamdu, Anita Kurniati Alachmad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In increase quality vulnerable roads in Indonesia damaged Because influenced by weather, water, load vehicle excess, and construction insufficient pavement​ fulfil requirements, required material add as much as you can increase strength and help repair construction road asphalt the Utilization material waste plastic in construction pavement become good alternative​ in in increase quality pavement road. Objective study This is For know How influence addition waste plastic type High Density Polyethylene (HDPE) against Marshall Laston AC-WC characteristics with variation rate HDPE plastic at 0%, 2%, 4%, and 6%. Marshall characteristics reviewed is mark density (density), VIM (void in mix), VMA (void mineral aggregate), VFA (void filled with asp halt), melting (flow), and stability. Method research used​ with method experiments in the laboratory and refers to Specification General Highways​ 2018. Research results shows the Marshall test on the mixture Laston AC-WC with addition rate HDPE plastic 0%, 2%, 4%, and 6% can be raise mark density (density), stability , VFA ( Void Filled with Asphalt), whereas For VIM (void in mix), VMA (Void Mineral Aggregate) and melt (flow) values experienced decline . Marshall parameter values obtained​​ fulfil standard Specification General Highways​ 2018. Percentage​ rate optimum asphalt (KAO) obtained is 6.0%, Marshall test of variation material plus waste plastic best value​ For density, melting (flow), stability, VIM , VMA, and VFA, namely at levels waste plastic 2%.